Basic quantum circuits for classification and approximation tasks - Wiśniewska, Joanna; Sawerwain, Marek; Obuchowicz, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
We discuss a quantum circuit construction designed for classification. The circuit is built of regularly placed elementary quantum gates, which implies the simplicity of the presented solution. The realization of the classification task is possible after the procedure of supervised learning which constitutes parameter optimization of Pauli gates. The process of learning can be performed by a physical quantum machine but also by simulation of quantum computation on a classical computer. The parameters of Pauli gates are selected by calculating changes in the gradient for different sets of these parameters.
Keywords: quantum circuits; data classification; supervised learning; qubits; qudits